A green approach for enhancing the hydrophobicity of UiO-66(Zr) catalysts for biodiesel production at 298 K. Issue 68 (12th November 2020) - Abou-Elyazed, Ahmed S.; Sun, Yinyong; El-Nahas, Ahmed M.; Yousif, Ahmed M.
Abstract : Recently, the incorporation of hydrophobicity on the surface of UiO-66(Zr) has received much attention due to the deactivation of hydrophilic active sites of UiO-66(Zr) upon water adsorption. Abstract : Recently, the incorporation of hydrophobicity on the surface of UiO-66(Zr) has received much attention due to the deactivation of hydrophilic active sites of UiO-66(Zr) upon water adsorption. In this work, we report UiO-66(Zr) catalysts with an assortment of surface hydrophobicities fabricated by the solvent-free method to elucidate the impact of the environment framing Lewis acid sites on their catalytic activity in the production of fatty acid methyl ester (biodiesel) via the esterification of fatty acids at room temperature with high selectivity (100%) and good recyclability. A detailed structural analysis of the materials by N2 sorption, FT-IR, SEM, XRD, water contact angle measurement, dynamic liquid scattering (DLS), NMR and TGA revealed the fabrication of stearic acid-grafted UiO-66(Zr) catalysts (10SA/UiO-66) with fine particle size and a highly hydrophobic network. 10SA/UiO-66(Zr) with enhanced hydrophobicity exhibited superior catalytic performance in the esterification of a fatty acid with a long alkyl chain compared with conventional solid acid catalysts and even liquid acid catalysts. Detailed kinetic studies corroborated that the adsorption of lipophilic acids at the Lewis acid sites besides the enhancement of wettability between the reactants was facilitated by the hydrophobic environment, thus significantly motivating the esterification reaction at room temperature. Furthermore, 10SA/UiO-66(Zr) showed good catalytic activity in the esterification of oleic acid in the presence of water (∼10% in the light of acid weight).